The Hernández-Pacheco Photographic Collection: A Gaze at the Spanish Colonies in Africa - Lérida Jiménez, Alba (Hispania Nova, 2023)
This paper will start with the theoretical reflection on photography as a historical message, to address the work carried out by the naturalist Eduardo Hernández-Pacheco, a fundamental figure in Spanish geology, paleontology and geography. In the first half of the 20th century he embarked, with his son Francisco Hernández-Pacheco, on several scientific expeditions that took him to some of the Spanish colonies in Africa: Sahara, Morocco or Equatorial Guinea. The aim is to analyze his personal photographic collection deposited in the Marqués de Valdecilla Historical Library, which contains a total of 400 photographs of the Spanish colonies in Africa and which portrays in detail the people who inhabited those places, their rugged landscapes and their different ways of life.
Keywords: Marqués de Valdecilla Historical Library; photography; Eduardo Hernández-Pacheco; Africa; Sahara; colonialism